Community and Identity in Contemporary Technosciences (2021)
This open access edited book provides new thinking on scientific identity formation. It thoroughly interrogates the concepts of community and identity, including both historical and contemporaneous analyses of several scientific fields. Chapters examine whether, and how, today's scientific identities and communities are subject to fundamental changes, reacting to tangible shifts in research funding as well as more intangible transformations in our society's understanding and expectations of technoscience. Authors: Karen Kastenhofer, Susan Molyneux-Hodgson, Clemens Blümel, Bettina Bock von Wülfingen, Béatrice Cointe, Carlos Cuevas-Garcia, Sarah R Davies, Alexander Degelsegger-Márquez, Juliane Jarke, Pierre-Benoît Joly, Marianne Noël, Benjamin Raimbault, Andrea Schikowitz, Sarah M. Schönbauer, Inga Ulnicane-Ozolina, Caitlin D. Wylie